Comparative transcriptomics reveal that adaptive evolution in immune genes drives the local adaptation and speciation of schizothoracine fish - Qi, Delin; Wu, Rongrong; Chao, Yan; Xia, Mingzhe; Chen, Qichang; Zheng, Zhiqin (bioRxiv, 2019)
Transcriptomic information can increase our understanding of the molecular processes underlying speciation. The schizothoracine fish, the largest and most diverse taxon within the Qinghai-Tibetan Plateau (QTP) ichthyofauna, are widespread in drainages throughout the QTP. These fish thus serve as an ideal model group with which to investigate how molecular evolution drives local adaptation during speciation. Here, we performed an interspecific comparative analysis of the transcriptomes of 13 schizothoracine fish species, and identified the key positively selected genes (PSGs) associated with significantly enriched functions and metabolite pathway acting on the specific lineages (or species) in the schizothoracine fish. We generated 64,637,602–83,968,472 sequence reads per schizothoracine fish species using Illumina sequencing, yielding 95,251–145,805 unigenes per species. We identified 52 out of 2,064 orthologous genes as candidate genes, which have probably been subject to positive selection along the whole schizothoracine fish lineage. Nine of these candidate genes were significantly enriched in key GO functions and metabolite pathways, all of which were associated with the immune system. The lineage-specific evolution test showed species-specific differences among the nine candidate PSGs, probably due to ecological differences among drainages, as well as among micro-habitats in the same drainage (e.g., benthic and pelagic). Here, we provide evidence that the adaptive evolution of immune genes, along with the uplift of the QTP, allowed new schizothoracine species to colonize ecologically novel environments or to exploit vacant ecological niches during speciation.